Controlled Synthesis of Multi‐Arm Star Polyether–Polycarbonate Polyols Based on Propylene Oxide and CO2. Issue 2 (11th November 2013) - Hilf, Jeannette; Schulze, Patricia; Seiwert, Jan; Frey, Holger; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> Multi‐arm star copolymers based on a hyperbranched poly(propylene oxide) polyether–polyol (hbPPO) as a core and poly(propylene carbonate) (PPC) arms are synthesized in two steps from propylene oxide (PO), a small amount of glycidol and CO2. The PPC arms are prepared via carbon dioxide (CO2)/PO copolymerization, using hbPPO as a multifunctional macroinitiator and the (R, R)‐(salcy)CoOBzF5 catalyst. Star copolymers with 14 and 28 PPC arms, respectively, and controlled molecular weights in the range of 2700–8800 g mol−1 are prepared (Mw/Mn = 1.23–1.61). Thermal analysis reveals lowered glass transition temperatures in the range of −8 to 10 °C for the PPC star polymers compared with linear PPC, which is due to the influence of the flexible polyether core. Successful conversion of the terminal hydroxyl groups with phenylisocyanate demonstrates the potential of the polycarbonate polyols for polyurethane synthesis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>